FACTORS THAT INFLUENCE COMPANY SUSTAINABILITY - Wiwik Pratiwi; Tikkos Sitanggang; Azahra Pratiwi Putri (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study aims to examine the effect of Green Manufacturing, Green Advertising and Environmental performance as measured by PROPER ratings on Corporate Sustainability as measured by the spread of Sustainability Report as measured by the GRI standard. In this study using secondary data, the population in the study were 125 companies which were manufacturing companies and the sample in this study using purposive sampling method there were 50 samples of company data that met the sample criteria obtained using certain criteria in PROPER participating companies listed on the IDX for the 2019-2023 period. The statistical method used in this research is panel data regression analysis, using the Eviews 13 measuring tool. The results in this study indicate that green manufacturing has a positive and significant effect on corporate sustainability, and environmental performance have a positive and insignificant effect on corporate sustainability. Meanwhile, green advertising has a negative and insignificant effect on company sustainability. The difference is that previous researchers used the Green Accounting variable, while this study uses the Green Manufacturing variable on Corporate Sustainability and this study using a dummy variable proxy for companies that disclose environmentally friendly production systems. The three factors jointly influence corporate sustainability, indicating that a holistic approach that includes various green aspects is more effective in encouraging corporate sustainability. Therefore, managers need to adopt a holistic sustainability strategy, ensuring good integration between various green aspects to achieve better sustainability and increase consumer confidence.